Sulfation of glycosaminoglycans and its Implications in human health and disorders - Costa, Diana Soares da (2017)
Sulfation is a dynamic and complex posttranslational modification process. It can occur at various positions within the glycosaminoglycan (GAG) backbone and modulates extracellular signals such as cellâ cell and cellâ matrix interactions; different sulfation patterns have been identified for the same organs and cells during their development. Because of their high specificity in relation to function, GAG sulfation patterns are referred to as the sulfation code. This review explores the role of GAG sulfation in different biological processes at the cell, tissue, and organism levels. We address the connection between the sulfation patterns of GAGs and several physiological processes and discuss the misregulation of GAG sulfation and its involvement in several genetic and metabolic disorders. Finally, we present the therapeutic potential of GAGs and their synthetic mimics in the biomedical field.